2021
DOI: 10.3390/nu13103301
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerides and Phospholipids from Egg Yolk Differently Influence the Immunostimulating Properties of Egg White Proteins

Abstract: As part of a whole egg, egg white proteins are embedded in a lipid matrix that could modify their presentation to the immune system and their allergenic properties. The present study examines the impact of the main egg lipid components, triacylglycerides and phospholipids, in the early events of sensitization to egg. To this end, BALB/c mice were exposed intragastrically to egg lipids and egg lipid fractions, alone and in mixtures with egg white proteins, and Th2-promoting and proinflammatory effects were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In line with our previous acute administration study (Pérez-Rodríguez et al, 2021) the present results also suggest that egg proteins combined with TG were preferentially absorbed through IECs, whereas PL contributed to the delivery of antigens to lymphoid organs. The different effect of triglycerides and phospholipids on antigen uptake was confirmed in the absorption of OVA, the most abundant and allergenic egg white protein (Benedé et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our previous acute administration study (Pérez-Rodríguez et al, 2021) the present results also suggest that egg proteins combined with TG were preferentially absorbed through IECs, whereas PL contributed to the delivery of antigens to lymphoid organs. The different effect of triglycerides and phospholipids on antigen uptake was confirmed in the absorption of OVA, the most abundant and allergenic egg white protein (Benedé et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, co‐administration of shorter chain triacylglycerols or other lipids that are preferentially taken up through Peyer's patches favored subsequent transport of proteins to the draining mesenteric lymph nodes and increased their immunogenicity (Li, Wang, et al., 2013). Moreover, a recent study reported that egg phospholipids reduce the solubility of egg white proteins in simulated duodenal fluid, impairing epithelial absorption and promoting antigen delivery to Peyer's patches (Pérez‐Rodríguez et al., 2021).…”
Section: Features That Impact Allergen Transport (Mie1‐3)mentioning
confidence: 99%